Pengembangan Media Audio Visual Berbasis Plotagon: Solusi Peningkatan Numerasi dan Efikasi Diri Siswa dalam Pembelajaran Matematika - Aliya Robi'ah (Universitas Muhammadiyah Magelang, 2026)
This study produces the final product of developing audiovisual-based learning media using the Plotagon application and identifies students' numeracy and self-efficacy. The study aims to determine the validity, practicality, and effectiveness of the learning media. This research applies the Research and Development (R&D) method in the process of developing learning media. The study involves all ninth-grade classes of MTs Negeri 1 Bangka in the 2025/2026 academic year, totaling 153 students, with class IXC consisting of 32 students as the research sample. The research instruments used include observation, document review, media expert validation questionnaires, material experts, language experts, and student self-efficacy questionnaires. The data analysis techniques used are quantitative descriptive and qualitative descriptive analysis. The results indicate that the learning media using the Plotagon application meet the criteria for being valid, practical, and effective. Students carried out numeracy tests in the learning process using the Plotagon application, achieving a classical completeness of 78% in the sample class with the school’s KKM score of 70. Then, the self-efficacy result reached 3.6, meaning the students’ self-efficacy reached a high category. Overall, with the development of valid, practical, and effective learning media, the use of audiovisual-based learning media using the Plotagon application can improve students' numeracy skills and self-efficacy.